Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai pada Badan Pendapatan Daerah Kabupaten Pringsewu - Riyadini Riyan Utami (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
One further factor affecting the performance of an employee is working discipline. Of the agency itself also plays a role in managing employees to comply with all rules, norms set by the agency so that the employees work with discipline and effective. Discipline is one's awareness and willingness to comply with all regulations and the organization of social norms in force. This research was conducted descriptive quantitative research type, type of research is intending to make a presentation in systematic, factual, and accurate information on the facts and the nature of a particular population. This study uses 44 research respondents. There are three variables in this study are: two (2) independent variables (X1 and X2) and 1 (one) in which the dependent variable of work discipline (X1) and motivation (X2) as independent variables and employee performance (Y) as the dependent variable. Accord by the data processing has been found that answers the following hypothesis; there are significant work discipline (X1) toward employee performance (Y) with the level of influence of 37.8%. There is the influence of work motivation (X2) toward employee performance (Y) with the level of influence of 31.1%. There is the influence of work discipline (X1) and work motivation (X2) by simultan toward employee performance (Y) with the level of influence of 48.8%.